2019
DOI: 10.1093/gerona/glz141
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Influence of Omega-3 Fatty Acids on the Plasma Metabolome of Healthy Older Adults

Abstract: Omega-3 polyunsaturated fatty acids (n3-PUFA) are well recognized for their potent triglyceride-lowering effects, but the potential influence of these bioactive lipids on other biological processes, particularly in the context of healthy aging, remains unknown. With the goal of gaining new insight into some less well-characterized biological effects of n3-PUFAs in healthy older adults, we performed metabolomics of fasting peripheral blood plasma collected from 12 young adults and 12 older adults before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Snap-frozen kidney cortex tissue from 6-week-old male SS Xdh+/+ (N = 5) and SS Xdh−/− (N = 4) rats were used for untargeted metabolomic analysis. The tissue was sent to the metabolomics core at the Mayo Clinic (Rochester, MN) ( Trushina et al., 2013 ; Xyda et al., 2020 ). The tissue was homogenized after adding 10 μl/mg of PBS, and 50μl of the homogenate was deproteinized and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Snap-frozen kidney cortex tissue from 6-week-old male SS Xdh+/+ (N = 5) and SS Xdh−/− (N = 4) rats were used for untargeted metabolomic analysis. The tissue was sent to the metabolomics core at the Mayo Clinic (Rochester, MN) ( Trushina et al., 2013 ; Xyda et al., 2020 ). The tissue was homogenized after adding 10 μl/mg of PBS, and 50μl of the homogenate was deproteinized and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Although the associations were weak, the inverse associations between fish or n-3 PUFAs and neopterin and the kynurenine/tryptophan ratio may suggest slightly lower immune activation with a higher n-3 PUFA intake, which happened in the majority of patients who consumed more than the current recommendation of 250 mg/day [96]. A recent study in 12 young adults and 12 older adults provided metabolomic insight into the biological effects of n-3 PUFA supplementation (3.9 g/day over a four-month period) on protein metabolism and the kynurenine pathway [97]. The authors observed significant increases in hydroxyproline following supplementation in older adults, which was in line with previously reported significant increases in muscle protein synthesis following n-3 PUFA supplementation in the same individuals [98].…”
Section: N-3 Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…The GWAS found in Mediterranean metabolic syndrome the association of FADS1/FADS2 locus and omega-3 polyunsaturated fatty acids and omega-6/omega-3 ratio, revealing a potential confounder explaining previous inconsistencies ( Coltell et al, 2020 ). As for the effect of fatty acids on a metabolic level, one recent study tested the influence of Omega-3 fatty acids in healthy old subjects and found its supplementation leads to reduction of total triglycerides, diacylglycerols, phospholipids, and triacylglycerols and very-low-density lipoproteins, whose elevations are associated with metabolic diseases ( Xyda et al, 2020 ). Animal studies have confirmed Omega-3 fatty acid provides cell signaling intermediate (specialized pro-resolving mediators) precursors for inflammation resolution in the adipose tissue microenvironment and elevates insulin sensitivity in the condition of MetS ( Carracedo et al, 2019 ; Kwon, 2020 ).…”
Section: Interventions For Mets Supported By “Big Data” Approachesmentioning
confidence: 99%